Parent-Implemented Trial-Based Functional Analysis for Young Children With ASD. (March 2019) - Gerow, Stephanie; Rispoli, Mandy; Gregori, Emily; Sanchez, Lisa
There is growing support for the use of trial-based functional analysis (TBFA) in applied settings. The purpose of the present study was to assess the accuracy and social validity of parent-implemented TBFAs. The participants were three young children (ages 3–7 years old) with autism spectrum disorder (ASD) and their mothers. Each mother implemented the TBFA with coaching from a behavior consultant. Following the TBFA, parent-implemented function-based interventions were evaluated using a multiple-probe across parent–child dyads design. Child challenging behavior decreased and communication increased following the implementation of the function-based intervention. TBFAs required approximately 5 to 7 hr of consultant time, and each mother rated the TBFA as socially valid. The results of this study indicate parent-implemented TBFAs may be an accurate and socially valid method to evaluate the function of challenging behavior in homes. The discussion includes implications for practice and directions for future research.